Characterization of antibody to the ferripyochelin-binding protein of Pseudomonas aeruginosa. - Sokol, P A (1986)
An outer membrane protein of Pseudomonas aeruginosa was previously shown to bind 59Fe-labeled pyochelin. Antibodies to the purified ferripyochelin-binding protein (FBP) were characterized by using a variety of assays. Anti-FBP cross-reacted with several P. aeruginosa isolates in an enzyme-linked immunosorbent assay. Anti-FBP significantly enhanced phagocytosis of P. aeruginosa by human polymorphonuclear leukocytes. In a serum bactericidal assay we observed no difference in viability between cells incubated with antiserum to FBP and cells incubated with preimmune serum. Anti-FBP immunoglobulin G inhibited both binding and uptake of 59Fe-labeled pyochelin by whole cells. Passive protection by anti-FBP was examined in experimental P. aeruginosa burn infections in mice. The protection provided by this antibody was strain dependent but lipopolysaccharide serotype independent.